A New Aromatic Glycoside from Morina longifolia Wall - H. Bodakhe, Surendra; Ram, Alpana; P. Pandey, Devi (Asian Journal of Chemistry, 2010)
A new aromatic glycoside characterized as 2,6-dihydroxy-5-methoxy-(3-C-glucopyranosyl) benzoic acid (1), was isolated along with four known compounds from aerial parts of Morina longifolia Wall. Its structure was determined on the basis of chemical and spectroscopic methods.